Cardiovascular Disease Burden in Rural Africa: Does HIV and Antiretroviral Treatment Play a Role?: Baseline Analysis of the Ndlovu Cohort Study. Issue 7 (9th April 2020) - Vos, Alinda G.; Barth, Roos E.; Klipstein‐Grobusch, Kerstin; Tempelman, Hugo A.; Devillé, Walter L. J.; Dodd, Caitlin; Coutinho, Roel A.; Grobbee, Diederick E.; ,
Abstract : Background: HIV is associated with an increased risk of cardiovascular disease (CVD) in high‐income countries. Little is known about the CVD burden in sub‐Saharan Africa, where 70% of the world's HIV‐positive population lives. This study aims to provide insight into the burden of CVD risk in a rural setting in sub‐Saharan Africa considering HIV infection and antiretroviral therapy (ART). Methods and Results: A cross‐sectional analysis was conducted of the baseline of the Ndlovu Cohort study including HIV‐negative and HIV‐positive participants in rural South Africa between 2014 and 2017. Information was collected on demographics, socioeconomic status, and CVD risk factors. Carotid intima‐media thickness measurement was performed. The influence of HIV and ART on the burden of CVD was determined by comparing HIV‐positive participants who were ART naive on first‐line or second‐line ART with HIV‐negative participants. In total, 1927 participants were included, of whom 887 (46%) were HIV positive and 54% women. The median age was 38 years. Overall, 690 participants (79%) were on ART, with 613 (89%) on first‐line and 77 (11%) on second‐line therapy. Participants with HIV had lower values for most of the CVD risk factors but higher C‐reactive protein levels than HIV‐negative participants. ART‐naive, HIV‐positive participants had similar carotid intima‐media thickness compared with HIV‐negative participants but carotid intima‐media thickness was increased for participants on ART aged 30 years and older compared with HIV‐negative participants. Conclusions: HIV‐positive participants presented with a favorable CVD risk profile compared with HIV‐negative participants. However, carotid intima‐media thickness was increased in HIV‐positive participants on ART, indicating a higher burden of subclinical CVD for the HIV‐positive population.